THE UNITED NATIONS’ APPROACH ON SECURITY SECTOR REFORM. THE CASE OF LIBYA - KRAFT-BIRIȘ, Paul (Studia Universitatis Babes-Bolyai Studia Europaea, 2019)
This article reviews the concept of Security Sector Reform and its application in conflict-afflicted countries – the case which is discussed being Libya. In the first section of the text, the emergence of the concept in the field of Security Studies is illustrated; additionally, the paper highlights the actors that actively engage in Security Sector Reform programs with a central focus on the United Nations. Challenges that the United Nations model face are later presented – with emphasis on the short-term mandates and the unrenewed as well as the universally applied Security Sector Reform guidelines. The last part of the article represents an analysis of the United Nations-led Security Sector Reform programme in Libya and the goal here is to illustrate how the challenges presented at the beginning of the article can be traced in the case of the northern-African country.